Self-Assembly versus Directed Assembly of Nanoparticles via Pulsed Laser Induced Dewetting of Patterned Metal Films - Fowlkes, Jason D. (2011)
A nanoscale, synthetic perturbation was all that was required to nudge a natural, self-assembly process toward significantly higher order. Metallic thin film strips were transformed into nanoparticle arrays by nanosecond, liquid phase dewetting. Arrays formed according to an evolving Rayleigh-Plateau instability yet nanoparticle diameter and pitch were poorly controlled. However, by patterning a nanoscale sinusoid onto the original strip edge a precise nanoparticle diameter and pitch emerged superseding the naturally evolving Rayleigh-Plateau instability.